Тепловое поле Донбасса - Гордиенко, В.В.; Гордиенко, И.В.; Завгородняя, О.В. (Геофизический журнал, 2015)
Розглянуто результати вивчення теплового потоку Донбасу. Визначено аномалії різної природи, проведено їх інтерпретацію. Побудовано теплову модель кори та верхньої мантії. Використано електричні термометри власної конструкції. Показано, що технологія буріння (без циркуляції промивальної рідини) та невеликий час проходки свердловин призводили до дуже швидкого відстою. Вже через кілька годин після завершення буріння протягом кількох діб спостерігалися незмінні температури вибою. Більшість визначень теплового потоку виконано за результатами вимірів температури вибою стандартними каротажними термометрами у процесі геофізичних випробувань свердловин. Як правило, відстой свердловин становив від кількох годин до кількох діб. Інструментальну похибку такої операції оцінено у перші десяті частки градуса. Головна похибка явно пов'язана зі спотвореннями температури.
За отриманими даними можна будувати карти теплового потоку та температури надр у масштабах 1:2 500 000-1:5 000 000. Наведено детальніші побудови для території Донбасу, де щільність сітки значно вища за середню по Україні. Інформацію про тепловий потік та глибинні температури доповнено картами геотермальних ресурсів території Донбасу. We estimate results of the study of deep heat flow of Donbas. Anomalies of different nature have been distinguished. Their interpretation has been conducted. The thermal model of the crust and upper mantle has been plotted. Self-constructed electrical thermometers have been applied. It was also shown, that the used drilling technology (without washing fluid circulation) and the short time of drilling provided a very short borehole "rest". Already in several hours after finishing drilling stable bottom borehole T were observed during several 24h terms. The main part of heat flow determinations were made by using the results of the borehole bottom Т measurements made by standard logging thermometers in the geophysical borehole logging. As a rule, the boreholes "rest" was from several hours to several days. Instrumental errors of this operation were repeatedly estimated and made the first tenth of a degree centigrade. The main error is clearly due to Т distortions. The data collected generally enable plotting heat flow HF and interior temperature maps scaled at 1:2 500 000 - 1:5 000 000. More detailed maps of the Donbas territory where the network density is well above the average one of the Ukraine have also been shown. The HF and deep temperature data are supplemented with the geothermal resource maps of the Donbas.